2020
DOI: 10.1039/c9ob02607j
|View full text |Cite
|
Sign up to set email alerts
|

FeCl3 mediated dimerization of dihydropyrrolo[2,1-a]isoquinolines and chlorination of tetrasubstituted pyrroles

Abstract: We have developed a mild FeCl3-mediated dimerization of dihydropyrrolo[2,1-a]isoquinolines through oxidative homocoupling (35–>99% yield) and chlorination of tetrasubstituted pyrroles (18–70% yield).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 79 publications
0
28
0
Order By: Relevance
“…In general, acceptable to moderate yields were obtained in most cases. Two possible reasons should account for the relatively low yields in this study: (1) Only moderate yield of SN2’ product can be formed in the reaction system, as amide group in the substrate may be involved in N‐allylic alkylation reaction; (2) Side reactions of desired products 4 , such as iron mediated/catalyzed dimerization and decomposition of products 4 via the formation of heteroarene cation radicals . Therefore, it is reasonable that compounds 4 would gradually diminish when heated at 150 °C for longer reaction time (monitored by TLC).…”
Section: Resultsmentioning
confidence: 97%
“…In general, acceptable to moderate yields were obtained in most cases. Two possible reasons should account for the relatively low yields in this study: (1) Only moderate yield of SN2’ product can be formed in the reaction system, as amide group in the substrate may be involved in N‐allylic alkylation reaction; (2) Side reactions of desired products 4 , such as iron mediated/catalyzed dimerization and decomposition of products 4 via the formation of heteroarene cation radicals . Therefore, it is reasonable that compounds 4 would gradually diminish when heated at 150 °C for longer reaction time (monitored by TLC).…”
Section: Resultsmentioning
confidence: 97%
“…Since methylthiomethylenation products have been reported as key intermediates by others and us for further transformations, compound 10 was tested under the optimal conditions. The desired product 2a can be obtained in 67% yield, demonstrating that the methylthiomethylenation product may also be as a crucial intermediate in the current reaction system (eq 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…It should be pointed out that it depends on the reaction conditions whether methylthiomethylenation product 10 could be converted to methylene-bridged pyrroloisoquinoline 2k . In our previous study, it was found that a NH 4 OAc/DMSO reaction system could be able to transform methylene-bridged product 2a to methylthiomethylenation product 10 irreversibly . In contrast, the methylthiomethylenation products were stable under the NH 4 OAc/DMSO system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…serotonin and decursivine derivatives. Recently, Cui reported the iron‐mediated methodology for the homocoupling of dihydropyrrolo[2,1‐a]isoqhuinolines [82] . Iron complexes in the cross‐dehydrogenative coupling of other heteroarenes require significant investigation to achieve sustainability in the field.…”
Section: Heteroarene‐heteroarene Couplingmentioning
confidence: 99%